Course of training has more than enough "administration of projects" for professionals of the concentration of Pichincha, Equator (Revista científica Olimpia, 2016)
The postgraduate education constitutes one of the roads to specify, to determine and to define new necessities that the different contexts respond in which a professional lends their services. In Ecuador, he/she has been able to verify, through different roads that the professionals of the Physical Culture don't possess the enough knowledge to negotiate the financing in the development of investigations and/or application of new methodologies of training, creation of other spaces of social interest, among others. Did this situation lead to formulate the following Scientific Problem: As promoting the knowledge it does have more than enough Administration of Scientific Projects, in the professionals of the Concentration of Pichincha, of Ecuador?. The Objective: To design a training course has more than enough Administration of Scientific Projects for the professionals of Physical Culture of the Concentration of Pichincha of Ecuador, propitiating a professional acting in correspondence with the demands for the current labor world. The methodological conception this sustained in the methods: Historical logical, Analysis and synthesis, system Focus, theoretical Modelation, you Interview, Analysis of documents, descriptive Statistic.
Keywords: administration, course, training